2010
DOI: 10.1002/jhm.702
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic approach and management of inpatient hyponatremia

Abstract: Hyponatremia is one of the most common electrolyte abnormalities encountered in clinical practice. The frequency of the disorder varies according to definition and clinical setting but has been reported to be present in 28% of patients upon hospital admission and in 7% of patients attending an ambulatory community clinic. 1 Increasing age, medications, various disease states, and administration of hypotonic fluids are among the known risk factors for the disorder.The mortality rate in hyponatremic patients is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…More commonly, the urine osmolality in hypotonic hyponatremia is some value .200 mOsm/kg resulting from the action of vasopressin to decrease free water excretion. Urine electrolytes can be used to assess volume status and determine whether the cause of increased vasopressin levels is secondary to a circulatory disturbance causing unloading of baroreceptors, or is baroreceptor independent as occurs in the syndrome of inappropriate antidiuretic hormone release (41).…”
Section: Urine Osmolalitymentioning
confidence: 99%
“…More commonly, the urine osmolality in hypotonic hyponatremia is some value .200 mOsm/kg resulting from the action of vasopressin to decrease free water excretion. Urine electrolytes can be used to assess volume status and determine whether the cause of increased vasopressin levels is secondary to a circulatory disturbance causing unloading of baroreceptors, or is baroreceptor independent as occurs in the syndrome of inappropriate antidiuretic hormone release (41).…”
Section: Urine Osmolalitymentioning
confidence: 99%
“…Electrolyte disturbances are commonly seen with chronic alcohol-use disorder in form of dysnatremias [46], hypokalemia, hypomagnesemia and hypophosphatemia. In one study; hypophosphatemia was found in about 50% of alcoholics who are admitted to hospital, while hypomagnesemia was found in up to 30% of alcoholics [7–9].…”
Section: Discussionmentioning
confidence: 99%
“…Measuring urine electrolytes prior to the infusion can help in predicting response. A urine Na ≤ 50 [11] or a urine Na + K/plasma Na < 0.5 [12] are more indicative of hypovolemic hyponatremia and suggest that serum Na will increase after the infusion of 1 -2 litres of 0.9% saline. In SIADH, the serum Na will decrease further after infusion of 0.9% saline, especially if the osmolality of the administered fluid is less than the urine osmolality [12].…”
Section: Discussionmentioning
confidence: 99%